SUBSURFACE SOIL INVESTIGATION IN THE AREA OF OPERATION OF A NATURAL GAS PROCESSING PLANT-X USING GEOELECTRIC RESISTIVITY METHOD DIPOLE-DIPOLE CONFIGURATION - RAMADHAN KHAZAI (NIM : 10211049), NOOR
Subsurface soil investigation is required to determine the geological conditions, soil characteristics, soil layer strength, density, and to know the nature of the soil corrosivity. This is needed to determine the type of foundation that will be used in building construction. When designing the building construction, it is necessary to have the petrophysical parameters, such as parameters of porosity, permeability and density of the subsurface. In this study, geoelectric resistivity with dipole-dipole configuration is used as geophysical survey method. The study was conducted on six tracks in the area of operation of a natural gas processing plant-x, while the resistivity values that were obtained from resistivity measurements would be used to determine the original soil layers, landfill and subsurface utilities. L1 track generated actual resistivity value range of 6.85x10-1 – 3.33x102 ohm.m with 8.4% error value. L2 track generated actual resistivity value range of 3.14x10-1 – 3.39x101 ohm.m with 23.3% error value. L3 track generated actual resistivity value range of 8.09x10-2 – 5.83 ohm.m with 22.3% error value. L4 track generated actual resistivity value range of 2.16 – 3.11x102 ohm.m with 20.8% error value. L5 track generated actual resistivity value range of 2.14 – 6.04x102 ohm.m with 20.5% error value. L6 track generated actual actual resistivity value range of 5.87 – 4.65x102 ohm.m with 20.8% error value.